Perpindahan Panas dan Penurunan Tekanan Pada Plat Rata Dengan Media Berpori (Porous) - Umurani, Khairul; ., Rahmatullah; Siregar, Ahmad Marabdi; Nasution, Arya Rudi; Pratama, Riza Fauzi (Rekayasa Material, Manufaktur dan Energi, 2023)
Convection heat transfer rate on a flat plate with a certain temperature can be increased by increasing the average heat transfer coefficient, increasing the surface area of heat transfer or both. In this study, stones and marbles were used as specimens of porous media with a diameter of 15 mm with a rock porosity of 43.8%, and marbles of 50.3% which were packed on a flat plate and tested in a rectangular air channel with an air velocity of 1 m /. s, 2 m / s, 3 m / s, 4 m / s, 5 m / s. Take experimental measurements on a heater set at 220 V. After steady conditions are established, record the temperature on the flat plate and the ambient air temperature. The highest Nusselt number occurs on flat plates with rock specimens of 69.025 and the highest convection heat transfer occurs on flat plates without porous media at 44.98 Watt, while convection heat transfer on flat plates with rock-porous media is lower than flat plates with porous media marbles. The friction factor decreases as the Reynold number increases. The greater the Reynold number, Nusselt number and the Convection heat transfer, followed by a decrease in the friction factor